Development of mobile robot in virtual reality environment for educational purpose - Saleh Al-Gahdari, Abdulaziz Shaif (2015)
Pulse compression The intelligent system can help a robot to navigate through the environment by itself. The need for such system has become of essence especially when quality and accuracy is demanded in delivering complete processes of work in specific time. This project has focused on building a mobile robot that will be able to navigate and avoid collision. This thesis has aimed for developing a mobile robot in virtual reality environment for educational purposes. A robot has been developed using SolidWorks simultaneously with a suitable virtual environment. The integration of the mobile robot with the virtual reality environment has been obtained in 3D editor in Simulink Matlab. The robot has been made to move randomly in order to track different scenario possibilities. It has been found that the angular velocity from the calculation is approximately same as the one set for the simulation, which confirmed that there is no delay in the time. It has been found that the shortest and longest distance between the mobile robot and the obstacles are 11 mm and 108.7 mm for the sensor range of 85 mm and 150 mm respectively. The mobile robot has navigated through the office virtual environment and avoided collision with the obstacles.